IMPLEMENTASI PENDEKATAN PMRI DAN KONTEKS ISLAM MELAYU PADA PENGEMBANGAN E-MODUL MATERI PRISMA DAN LIMAS BERBASIS CANVA - Nanda Nabila Al Jannah; Muhammad Win Afgani; Retni Paradesa (Faktor : Jurnal Ilmiah Kependidikan, 2023)
This study aims to determine the potential effect of applying the PMRI approach and the context of Malay Islam on the development of prism and pyramid material E-Modules. This research includes applied research which consists of three major stages, namely the planning stage, the refinement stage and the implementation stage. The application of the e-module was carried out with the subject of class IX students at SMP Negeri 54 Palembang. From the results of the research comments and suggestions from the e-module refinement stage, it was found that the developed e-module was feasible to be applied to students and the developed e-module had a potential effect by producing a completeness percentage of 83.33%.